2015
DOI: 10.7863/ultra.34.8.1385
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Positron Emission Tomography/Computed Tomography and Ultrasound Imaging for Detection of Internal Mammary Lymph Node Metastases in Patients With Breast Cancer and Pathologic Correlation by Ultrasound‐Guided Biopsy Procedures

Abstract: Although PET/CT is the best noninvasive method for evaluating internal mammary LN metastases, US is also useful if internal mammary LN evaluation is routine during standard US surveillance of patients with breast cancer. Additionally, US-guided biopsies could be performed immediately on any suspected metastases and yield a high positive rate without serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Previous studies have demonstrated that PET/CT is superior to conventional diagnostic techniques for detection of internal mammary LN metastases [ 21 22 ]. An et al [ 7 ] reported that PET/CT-positive internal mammary LNs were defined as those with an uptake greater than the adjacent background activity of the pectoralis muscle or the intercostal space along the lateral sternal border. In their study, there were statistically significant differences in maximum standardized uptake values from PET/CT between the metastatic and benign IMLN groups ( p =0.002), the mean maximum standardized uptake value of metastatic and benign IMLNs being 3.53±1.79 and 1.06±1.09, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that PET/CT is superior to conventional diagnostic techniques for detection of internal mammary LN metastases [ 21 22 ]. An et al [ 7 ] reported that PET/CT-positive internal mammary LNs were defined as those with an uptake greater than the adjacent background activity of the pectoralis muscle or the intercostal space along the lateral sternal border. In their study, there were statistically significant differences in maximum standardized uptake values from PET/CT between the metastatic and benign IMLN groups ( p =0.002), the mean maximum standardized uptake value of metastatic and benign IMLNs being 3.53±1.79 and 1.06±1.09, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…If pathologic examination was not performed, benign IMLNs were defined as showing 1 year of stability on MRI or no fluorodeoxyglucose (FDG) uptake on positron emission tomography computed tomography (PET/CT) (n=18). In contrast, malignant IMLNs were defined as showing FDG uptake greater than that of the adjacent background activity (determined in regions such as the pectoralis muscle, the intercostal space along the lateral sternal border or the mediastinal blood pool), increased FDG uptake on follow up PET/CT, an increased in size during the follow-up period, or a decrease in size after chemotherapy or radiation treatment (n=31) [ 7 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One research showed that the sensitivity of detecting the metastasis of internal mammary lymph nodes in breast cancer was 96.7%, while 92.9% in CEUS and PET/CT, respectively [20]. CEUS could present lymph nodes images as well as PET/CT in regional lymph nodes of lymphoma patients [21]. In addition, CEUS has the advantage of being inexpensive and nonradioactive.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence can be detected by patients themselves, surgeons, or follow‐up using ultrasound (US) or other imaging techniques, 7,8 Ultrasound and US‐guided fine‐needle aspiration biopsy and core biopsy are valuable for the assessment of both palpable and clinically occult recurrent BCa in autogenous myocutaneous flap breast reconstructions 9,10 . However, fine‐needle aspiration biopsy could give false‐negative results, and not all patients can receive biopsy because of substantial complications, including local hemorrhage, surrounding tissue injury, local infection, and needle tract metastasis, although such complications are uncommon 11 …”
mentioning
confidence: 99%